Homonormativity, queer capital and the Hong Kong Lesbian and Gay Film Festival - Xie, Heshen (2022)
As the first and longest-running queer film festival in East Asia, the Hong Kong Lesbian and Gay Film Festival (HKLGFF) was established in 1989. Since 2000, the HKLGFF has gradually commercialised, transforming into a self-sustained, market-driven queer film festival. Examining the operation of the HKLGFF offers insights into the queer film festivals that have undergone commercialisation around the world. Meanwhile, the examination of HKLGFF can reveal how small-scale queer film festivals interact with other (queer) film festivals regionally and globally. Focusing on the festival’s operations from 2016 to 2020, I argue that under the neoliberal trend in the global queer film festival circuit, by privileging middle-class gay identity and commercial interests, the HKLGFF reproduces homonormativity, which characterises the consumption-oriented queer culture in Hong Kong. The thesis adopts a combined methodology, including semi-structured interviews, content analysis and secondary data analysis. The thesis contextualises the HKLGFF in terms of the historical development of the festival itself, in terms of the relationship with the global queer film festival circuit, and in terms of the territory of Hong Kong. This thesis also investigates how the festival operation reproduces homonormativity through its programming and its targeting of and affordances for audiences. Overall, this thesis expands the concept of homonormativity and interrogates it to all aspects of festival organisation and provides a framework to explore the specificity of a queer film festival through an analysis of the dual relationship between the festival and its local context as well as the global queer film festival circuit. This thesis also extends the discussion of the film festival circuit by mapping the broader picture of the global landscape of queer film festivals as well as investigating how the global queer film festival circuit influences the operation of small-scale queer film festivals in the Global South.